Ras promotes germline stem cell division in Drosophila ovaries. - Zhang, Q.; Wang, Y.; Bu, Z.; Zhang, Y.; Zhang, Q.; Li, L.; Yan, L.; Wang, Y.; Zhao, S. (Stem cell reports, 2024)
The Ras family genes are proto-oncogenes that are highly conserved from Drosophila to humans. In Drosophila, Ras[V12] is a constitutively activated form of the Ras oncoprotein, and its function in cell-cycle progression is context dependent. However, how it influences the cell cycle of female germline stem cells (GSCs) still remains unknown. Using both wild-type GSCs and bam mutant GSC-like cells as model systems, here we determined that Ras[V12] overexpression promotes GSC division, not growth, opposite to that in somatic wing disc cells. Ras performs this function through activating the mitogen-activated protein kinase (MAPK) signaling. This signaling is activated specifically in the M phase of mitotic germ cells, including both wild-type GSCs and bam mutant GSC-like cells. Furthermore, Ras[V12] overexpression triggers polyploid nurse cells to die through inducing mitotic stress. Given the similarities between Drosophila and mammalian GSCs, we propose that the Ras/MAPK signaling also promotes mammalian GSC division.